Edukasi Urban Farming Budidaya Sistem Hidroponik - Ismail, Ismail; Hartati, hartati (Jurnal Abdi Negeriku, 2022)
The conversion of agricultural land in urban areas is increasing along with the increasing demand for residential land. Urban farming is an urban farming program by utilizing available land around the residence or yard. One of the strategic activities that can be carried out is urban farming education for hydroponic agriculture for the educated young generation. This Community Partnership Program was held with partners from Sekolah Menengah Atas Insan Cendekia Syech Yusuf  Pattallassang  Gowa. The problem faced by partners is the lack of knowledge and skills in hydroponic farming systems. The activity was carried out with the aim of increasing the knowledge and skills of partners about hydroponic system farming. To achieve this goal, the methods of lectures, demonstrations, discussions, questions and answers, and mentoring are used. The results achieved are: 1) partners have good knowledge in hydroponic system vegetable cultivation, and 2) partners have sufficient skills to carry out hydroponic system cultivation.